Viruses in chronic rhinosinusitis: a systematic review - Kumar, Nitish; Brar, Tripti; Kita, Hirohito; Marks, Lisa A.; Miglani, Amar; Marino, Michael J.; Lal, Devyani (Frontiers in Allergy, 2023)
Background Unlike acute rhinosinusitis (ARS) which is mostly viral in etiology, the role of viruses in chronic rhinosinusitis (CRS) remains unclear. Viruses may play a role in initiation, exacerbations or perpetuate chronic inflammatory responses in the sinonasal mucosa. Research needs to characterize whether viruses are part of the normal sinonasal microbiome, colonizers or pathogenic. Methods Systematic review of the English literature was conducted. Following databases were searched with an initial search conducted in November 2021 and then updated through June 2023: Ovid Medline (1946 to present), Ovid Embase (1988 to present), Scopus (2004 to present) and Web of Science (1975 to present). MeSH (Medical Subject Headings) terms included: viruses, virus diseases, sinusitis, and rhinovirus. Keywords: virus, viral infection*, sinusitis, rhinovirus, chronic rhinosinusitis, CRS, respiratory virus, respiratory infection*, and exacerbat*. A supplementary search was conducted through September 2023: Ovid Medline (1946 to present), Epub Ahead of Print, In-Process & Other Non-Indexed Citations and Ovid MEDLINE(R) Daily. Keywords used were: virus, viral infection*, sinusitis, chronic rhinosinusitis, CRS, respiratory virus, respiratory infection*, and exacerbat*. Results Thirty studies on viruses in CRS met inclusion criteria for full review. These included 17 studies on prevalence of virus in CRS, 5 examining probable causes of host susceptibility to viral infections in CRS, and 8 studies examining pathological pathways in viral association of CRS. The prevalence of viruses in nasal specimens of CRS subjects was higher as compared to controls in most studies, though a few studies showed otherwise. Rhinovirus was the most common virus detected. Studies showed that viruses may be associated with persistent hyper-responsiveness in the sinonasal mucosa, susceptibility to bacterial infections, upregulation of genes involved in the immune response and airway remodeling as well as CRS exacerbations. Presence of viruses was also associated with worse symptom severity scores in CRS subjects. Conclusion Most data show higher presence of viruses in nasal and serum samples of CRS subjects as compared to controls but their exact role in CRS pathophysiology in unclear. Large studies with longitudinal sampling at all disease phases (i.e., prior to disease initiation, during disease initiation, during disease persistence, and during exacerbations) using standardized sampling techniques are needed to definitively elucidate the role of virus in CRS.